Tháng Năm 19, 2024

Rút gọn biểu thức \(A = 2\sqrt {{{\left( {2 – \sqrt 5 } \right)}^2}} + \sqrt {20} – 20\sqrt {\frac{1}{5}} \). A \(A = – 4\). B \(A = 4\). C \(A = – 4 \sqrt {5}\). D \(A = 4 \sqrt {5}\).

Rút gọn biểu thức \(A = 2\sqrt {{{\left( {2 – \sqrt 5 } \right)}^2}} + \sqrt {20} – 20\sqrt {\frac{1}{5}} \).

A \(A = – 4\).

B \(A = 4\).

C \(A = – 4 \sqrt {5}\).

D \(A = 4 \sqrt {5}\).

Hướng dẫn Chọn đáp án là: A

Phương pháp giải:

Sử dụng hằng đẳng thức \(\sqrt {{A^2}} = \left| A \right|\).

Lời giải chi tiết:

\(A = 2\sqrt {{{\left( {2 – \sqrt 5 } \right)}^2}} + \sqrt {20} – 20\sqrt {\frac{1}{5}} \)

\(\begin{array}{l}A = 2\left| {2 – \sqrt 5 } \right| + \sqrt {4.5} – 4.5.\frac{1}{{\sqrt 5 }}\\A = 2\left( {\sqrt 5 – 2} \right) + 2\sqrt 5 – 4\sqrt 5 \,\,\,\,\left( {Do\,\,2 – \sqrt 5 < 0} \right)\\A = 2\sqrt 5 – 4 + 2\sqrt 5 – 4\sqrt 5 \\A = – 4\end{array}\)

Vậy \(A = – 4\).